Pemanfaatan Gelombang Elektromagnet Extremely Low Frequency (Elf) Dalam Ketahanan Pangan - Shabitna, Flapreliani Syafa; ., Yushardi; ., Sudarti (Jurnal Pendidikan, Sains Dan Teknologi, 2023)
Physics is considered an important subject that is taught as a subject in itself with various considerations. Physics is seen as both a process and a product, so successful physics learning requires attention to effective and efficient learning. The utilization of Extremely Low Frequency (ELF) electromagnetic waves has great potential in the field of food security. ELF waves have low-frequency characteristics that create a unique potential to influence microbial activity and nutrient availability in improving food security productivity. ELF waves can be used to increase the productivity and quality of food crops, as well as extend the shelf life of food products. Thus, the utilization of ELF waves can help in achieving sustainable food security. In an effort to improve food security, it is necessary to innovate and develop technology that can support agricultural productivity. More research is still needed to fully understand the mechanism of action of ELF waves and how best to use them in agricultural and food processing practices.